Beliefs, Mental Health, Healthy Lifestyle Behaviors and Coping Strategies Used by College Students During the COVID-19 Pandemic - Bernadette Mazurek Melnyk; Alai Tan; Andreanna Pavan Hsieh; Megan Amaya; Erica Regan; Leanne Stanley (The Ohio State University Libraries, 2021)
Background: The COVID-19 pandemic has added substantial stress to the college student experience that could escalate the already existing student mental health crisis. Institutions of higher education have been called to explore ways in which they can promote and support the whole student. Objective: To describe college students' beliefs about returning to campus, safety practices, mental health, and strategies used to cope with the COVID-19 pandemic. Methods: A descriptive survey was emailed to a stratified random sample of undergraduate, graduate, and professional students (N = 14,459) from a large public Mid-west university. The survey measured beliefs about returning to campus and safety practices, mental health status (anxiety, depression, and burnout), and coping strategies used to deal with the stress of the pandemic. Results: The response rate was 30.7%. Thirty percent of students were not confident about returning to campus safely. Thirty-nine percent met the cut-off for clinical anxiety, 24% for depression, and 39.9% for burnout. A substantial percentage used unhealthy lifestyle behaviors to cope with pandemic stress. Conclusion: Institutions of higher education must accelerate mental health screening and services along with evidence-based preventive interventions and wellness programming for students.